Incidence of autoimmune diseases in a nationwide HIV/AIDS patient cohort in Taiwan, 2000–2012. Issue 4 (2nd September 2016) - Yen, Yung-Feng; Chuang, Pei-Hung; Jen, I-An; Chen, Marcelo; Lan, Yu-Ching; Liu, Yen-Ling; Lee, Yun; Chen, Yen-Hsu; Chen, Yi-Ming Arthur
Abstract : Objectives: It is not known if the incidences of autoimmune diseases are higher in individuals living with HIV infection or AIDS. Our study investigated the incidences of autoimmune diseases among people living with HIV/AIDS (PLWHA) in Taiwan during 2000–2012. Methods: The Taiwan National Health Insurance Research Database was used to identify PLWHA. The incidence densities of systemic and organ-specific autoimmune diseases were calculated, and age-adjusted, sex-adjusted and period-adjusted standardised incidence rates (SIRs) were obtained by using two million people from the general population as controls. To examine the effects of highly active antiretroviral therapy (HAART) on the incidence of autoimmune diseases, the incidence densities and SIRs of autoimmune diseases were calculated after stratifying PLWHA by HAART status. Results: Of the 20 444 PLWHA identified, the overall mean (SD) age was 30.1 (11.0) years; 67.2% of the subjects received HAART. As compared with the general population, SIRs were higher for incident Sjögren syndrome (SIR=1.64; 95% CI 1.24 to 2.13), psoriasis (SIR=2.05; 95% CI 1.67 to 2.48), systemic lupus erythematosus (SLE) (SIR=2.59; 95% CI 1.53 to 4.09), autoimmune haemolytic anaemia (SIR=35.06; 95% CI 23.1 to 51.02) and uveitis (SIR=2.50; 95% CI 2.05 to 3.02), but were lower for incident ankylosing spondyloarthritis (SIR=0.70; 95% CI 0.48 to 0.99). When the effect of HAART on incident autoimmune diseases was considered, PLWHA who received HAART had higher SIRs for psoriasis, autoimmune haemolytic anaemia and uveitis, but had lower risks of rheumatoid arthritis (RA) and ankylosing spondyloarthritis. In contrast, PLWHA who did not receive HAART had higher SIRs for Sjögren syndrome, psoriasis, RA, SLE, scleroderma, polymyositis, autoimmune haemolytic anaemia and Hashimoto's thyroiditis. Conclusions: PLWHA had higher risks of incident Sjögren syndrome, psoriasis, SLE, autoimmune haemolytic anaemia and uveitis.